The Effectiveness of Content Marketing Strategies in Enhancing Brand Awareness of Local Coffee Products Among Indonesian Millennials - Syah Amin Albadry; Agus Surya Bharmawan; Eko Nur Hermansyah; Erni Junaida; Afnina (PT Mattawang Mediatama Solution, 2025)
Indonesia’s coffee industry has rapidly expanded, yet local coffee brands face challenges in differentiating themselves and building strong brand awareness among digitally savvy millennials. This study examines the effectiveness of content marketing strategies in enhancing brand awareness of local coffee products among Indonesian millennials. Using a quantitative explanatory approach, data were collected from 350 respondents who are active social media users and consumers of local coffee. The analysis was conducted with SPSS 26, applying validity, reliability, and multiple regression tests to evaluate four core dimensions of content marketing: content quality, relevance, posting consistency, and digital interactivity. The findings reveal that all four dimensions significantly and positively influence brand awareness, with content quality emerging as the most dominant factor. High-quality content establishes credibility and trust, while relevant and interactive content fosters emotional engagement and consumer participation. Posting consistency contributes to sustained visibility and recognition, reinforcing long-term brand retention in digital spaces. Theoretically, the study expands the understanding of digital brand communication by emphasizing the interaction between emotional and informational dimensions of marketing content. Practically, it suggests that local coffee brands should prioritize integrated content marketing strategies combining authenticity, creativity, and data-driven planning. Furthermore, consistent storytelling reflecting Indonesia’s cultural identity can transform local coffee branding from a promotional activity into a cultural narrative that enhances national pride and competitiveness. Overall, this study concludes that content marketing is not only a promotional mechanism but also a strategic framework for building enduring brand awareness and loyalty in Indonesia’s digital economy.